An isolated epileptic seizure elicits learning impairment which could be prevented by melatonin - Mareš, Jan; Pometlová, Marie; Deykun, Kateryna; Krýsl, David; Rokyta, Richard (Epilepsy & behavior, 2012)
We tested the relation between a single short tonic-clonic seizure elicited by flurothyl vapors and changes of learning in Morris water maze (MWM) in Wistar rats. Oxidative stress usually accompanies seizures. Large melatonin doses were applied immediately before and after seizures to test consequences on learning impairment. One hour of hypobaric hypoxia (8000 m) three days prior to the seizure served as an activator of intrinsic antioxidant systems. Learning in MWM (7 days) started 24 h after seizures. Following seizures, latencies in MWM were longer than in controls and were shortened by hypoxia and preventive melatonin application. Melatonin was also applied before hypoxia to influence free radical (FR) production and intrinsic antioxidant activation. Some behavioral characteristics were changed and preconditioning effect of hypoxia was reduced. Melatonin after seizure (150 s and 6 h) had negligible effect. Results allow us to hypothesize about the role of FR and the beneficial effect of melatonin on the behavioral consequences of seizures.
Keywords: Seizures; Flurothyl; konvulziva; Maze Learning; melatonin; bludiště - učení; hematoencefalická bariéra; Blood-Brain Barrier; analýza rozptylu; záchvaty; Convulsants; poruchy učení; Analysis of Variance; krysa rodu Rattus; Automatism; Hypoxia; Antioxidants; zvířata; časové faktory; hypoxie; antioxidancia; Reaction Time; Male; reakční čas; flurothyl; Learning Disabilities; Rats; Animals; automatismus; mužské pohlaví; Disease Models, Animal; Time Factors; modely nemocí na zvířatech; Melatonin